2020
DOI: 10.1017/s0033291720001890
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus conspiracy beliefs, mistrust, and compliance with government guidelines in England

Abstract: Background An invisible threat has visibly altered the world. Governments and key institutions have had to implement decisive responses to the danger posed by the coronavirus pandemic. Imposed change will increase the likelihood that alternative explanations take hold. In a proportion of the general population there may be strong scepticism, fear of being misled, and false conspiracy theories. Our objectives were to estimate the prevalence of conspiracy thinking about the pandemic and test associations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

55
636
7
29

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 581 publications
(786 citation statements)
references
References 26 publications
55
636
7
29
Order By: Relevance
“…Differences in the basic trust of officials because of cultural factors as well as recent political conflicts may have contributed to these results. It was reported very recently that an alarming number of individuals in England believe conspiracy theories about COVID-19, and these theories are associated with less adherence to official guidelines for precautionary behaviors [22]. On the contrary, we observed that the questionnaire respondents who had an acquaintance who was infected with the virus were likely to trust official information about COVID-19.…”
Section: Discussioncontrasting
confidence: 63%
“…Differences in the basic trust of officials because of cultural factors as well as recent political conflicts may have contributed to these results. It was reported very recently that an alarming number of individuals in England believe conspiracy theories about COVID-19, and these theories are associated with less adherence to official guidelines for precautionary behaviors [22]. On the contrary, we observed that the questionnaire respondents who had an acquaintance who was infected with the virus were likely to trust official information about COVID-19.…”
Section: Discussioncontrasting
confidence: 63%
“…The relationship between mistrust, paranoia-like thoughts, and adherence to medical or epidemiological recommendations has been described in recent research ( Freeman et al, 2020 ; Marinthe, Brown, Delouvée, & Jolley, in press), where paranoia-like and conspiracy beliefs in England and France are associated with lower adherence to safety guidelines. Importantly, believing in conspiracy theories is associated negatively with trust towards science in general ( Lewandowsky, Oberauer, & Gignac, 2013 )⁠.…”
Section: Introductionmentioning
confidence: 94%
“…Quarantine adherence was linked to socio-cultural norms and perceived pro-social character of isolation, perceived benefits of quarantine, perceived risk of disease outbreak and trust in government ( Webster et al, 2020 )⁠. We may expect that people with high levels of general interpersonal mistrust (e.g., having exaggerated paranoia-like thoughts) and perceiving epidemiological threat as illusionary, benign or a conspiracy, would be less inclined towards adherence to safety guidelines ( Freeman et al, 2020 ). Recently, all these factors may be operating even more intensively due to the high level of uncertainty and related stress during COVID-19 epidemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported very recently that an alarming number of individuals in England believe conspiracy theories about COVID-19, and these theories are associated with less adherence to o cial guidelines for precautionary behaviors. 22 On the contrary, we observed that the questionnaire respondents who had an acquaintance who was infected with the virus were likely to trust o cial information about COVID-19. Considering these results, the residents of Japan are potentially vulnerable to conspiracy theories in part because of the rare experience of an acquaintance's infection, although there is no evidence suggesting the spread of COVID-19 conspiracy theories in Japan.…”
Section: Discussionmentioning
confidence: 72%